Legal Basis for the Use of Electronic Media as a Means of Transaction in Indonesia - Muhammad, Ade Sultan; Suparidho, Febrihadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
As a developing country, particularly in the fields of science and technology, it is undeniable that the existence of information technology, in this case various electronic media, has become the basis for people to conduct various transactions in order to fulfill all basic needs and certain desires, such as purchasing equipment and even vehicles. In Indonesia, there are various regulations governing transactions carried out electronically, although some of them do not directly regulate the implementation of electronic transactions.